Cardioembolic stroke in patients with atrial fibrillation - Pramanasari, Indra; Alexander, Nick (International Journal of Research in Medical Sciences, 2022)
Stroke is a neurological emergency in the form of disturbances in brain function that occur suddenly, it can be focal or global, which lasts for 24 hours or more and even causes death, with no other obvious cause other than vascular disorders. Strokes are generally divided into two main categories: ischemic stroke and hemorrhagic stroke. Atrial fibrillation (AF) is a cardiac arrhythmia and is often associated with stroke, dementia, and death. In our case, an 81-year-old woman came to the ED complaining of sudden loss of consciousness with GCS E2V1M5. A non-contrast CT scan of the head revealed cerebral atrophy and senile cerebellum accompanied by suspicion of infarction in the left globus pallidus. The ECG results showed an irregular rhythm (irregular P-P) leading to AF. AF is a high-risk factor for stroke because of impaired blood pumping, so the risk of clots forming which can then escape and flow to the brain causes blockage of blood flow to the brain and stroke occurs. It is therefore important for routine treatment and control of high-risk patients with heart rhythm disorders such as AF to prevent embolic strokes.